Microwave-assisted one-pot synthesis of polycyclic 4-quinolone derivatives - Muscia, Gisela Celeste (2013)
A microwave-assisted solvent-free one-pot method to afford 1,2,3,4-tetrahydroacridines-9-one derivatives was developed, with shorter reaction time and from easily available starting materials compared to the known methods.